Factors affecting the use of e-commerce in creative industries: Empirical evidences from SMES in Jabodetabek-Indonesia - Donny Oktavian Syah; Rambat Lupiyoadi; Adi Pramudita Tjiptadi (Jurnal Siasat Bisnis, 2016)
The goal of this research is to identify factors that influences: organizational readiness, the external pressure, the ease of using, and final factor benefit that can be obtained from the use of e-commerce in SMEs Creative Industries in Jabodetabek.Our analysis demonstrate that there is a relationship between the organizational readiness, external pressure, the ease of using, and the benefits of e-commerce in SMEs Creative Industries in Jabodetabek city (Jakarta, Bogor, Depok, Tangerang, and Bekasi), Indonesia. In addition, the research found that when e-commerce was applied both the organizational readiness improved, and provided a clear benefit to the SMEs that adopted it. On the other hand, the external pressure and the perceived ease of use did not prove to have any significant effect in SMEs Creative Industries in Jabodetabek.